Analysis of International Legal Documents Adopted Within the Framework of the Sco (Eurasian Research Bulletin, 2023)
Among the main goals and objectives of the SCO economic agenda is to promote inclusive and balanced economic growth, social and cultural development, and integration into the global economy in the region through joint actions based on equal partnership to steadily improve living standards and conditions of peoples of member states and coordinate approaches.